(untitled) (Construction Economics and Building, 2012)
There is an increase in the number of construction projects experiencing extensive delays leading to exceeding initial time and cost budget. This paper reviews 41 studies around the world which surveyed the delay factors and classified them into Groups. The main purpose of this paper is to review literature, each of which have categorized the causes that are responsible for time delays and cost overrun in projects. The collected list has 113 causes for delays categorized in to 18 different groups. Most of the researches have analysed the responses from the Questionnaire survey. The collected data are used to rank the problem. The data are further used to investigate and analyse Important Index, Frequency Index, Severity Index, Relative Important Index, Relative Importance Weight, Weighted Average, Mean, Standard Deviation and Variance. The collective comparison has revealed that the ranking given by all the researchers is not the same. Further each and every study has different rank ratings for the different group of the delays. This review paper attempts to provide an updated compilation of the earlier studies on ranking of the delay causers, which are never similar and constant for universal projects. It is concluded that a separate study is required for identifying the factors causing delay for projects operated in Sabah, East Malaysia.